Strategies for disseminating recommendations or guidelines to patients: a systematic review. (December 2015) - Schipper, K.; Bakker, M.; De Wit, M.; Ket, J.; Abma, T.
Abstract Background The aim of this systematic literature review was to assess what dissemination strategies are feasible to inform and educate patients about recommendations (also known as guidelines). Methods The search was performed in February 2016 in PubMed, Ebsco/PsycINFO, Ebsco/CINAHL and Embase. Studies evaluating dissemination strategies, involving patients and/or reaching patients, were included. A hand search and a search in the grey literature, also done in February 2016, were added. Searches were not restricted by language or publication type. Publications that referred to (1) guideline(s) or recommendation(s), (2) dissemination, (3) dissemination with patients/patient organisations and (4) dissemination to patients/patient organisations were included in this article. Criteria 1 AND 2 were mandatory together with criteria 3 OR 4. Results The initial search revealed 3753 unique publications. Forty-seven articles met the inclusion criteria and were selected for detailed review. The hand search and grey literature resulted in four relevant articles. After reading the full text of the 47 articles, 21 were relevant for answering our research question. Most publications had low levels of evidence, 3 or 4 of the Oxford levels of evidence. One article had a level of evidence of 2(b). This article gives an overview of tools and strategies to disseminate recommendations to patients. Key factors of success were a dissemination plan, written at the start of the recommendation development process, involvement of patients in this development process and the use of a combination of traditional and innovative dissemination tools. The lack of strong evidence calls for more research of the effectiveness of different dissemination strategies as well as the barriers for implementing a strategic approach of dissemination. Conclusion Our findings provide the first systematic overview of tools and strategies to disseminate recommendations to patients and patient organisations. Participation of patients in the whole process is one of the most important findings. These findings are relevant to develop, implement and evaluate more (effective) dissemination strategies which can improve health care.